An analysis of whether Mozambique can gain greater participation in the natural gas value chain - Bangure, Kudzanayi (Graduate School of Development Policy and Practice, 2021)
The African continent possesses a wealth of natural mineral resources. Arguments have been put forward that these natural mineral resources can be one of the potential solutions to unlocking the challenge of underdevelopment and pervasive poverty in many African countries. Understanding how African countries can gain greater benefit from these mineral resources was the emphasis of this dissertation. Focus was placed specifically on the Mozambique natural gas sector. A case study methodology was employed with the purpose of determining whether Mozambique could gain greater participation in its natural gas value chain. Empirical and theoretical literature around mineral resources management including leading theories such as the resource curse were reviewed as key points of departure. A detailed analysis of historic natural gas projects executed in Mozambique, the legislative framework, contracts, and institutional and capacity demands then followed as a core part of the analysis. Finally, the study leaned on in-depth interviews with industry experts to understand the legal, policy, and technical barriers that could hinder Mozambique from gaining greater participation in the natural gas value chain. Key findings of the study pointed to the inadequacies of existing laws and contract provisions to deliver the vision of greater participation, barriers to entry such as high upfront capital requirements, and internal institutional and technical capacity gaps exemplified by the reliance on external technical assistance from partners such the World Bank. The study concluded that greater participation in the natural gas value chain could not be achieved through Mozambique legislating its way into upstream and midstream activities alone, rather, a progressive approach to gain greater participation was required, initially starting with increased participation in downstream activities through domestic gas to unlock industrialisation.